RANCANG BANGUN SISTEM INFORMASI INVENTORY PADA SALONKECANTIKAN - Elly Mufida; Eva Rahmawati; Hylenarti Hertiana (Jurnal Mantik Penusa)
The company or business unit utilizes the role of the internet for corporate activities, applications supporting corporate activities that have been made have started web-based both related to administration, finance, marketing, and management of goods or inventory so that information can be more quickly and easily accessed anywhere . Inventory system is a thing that is familiar to companies. But inventory problems often become obstacles. Handling of data that is still done using a manual system results in frequent errors. In the development of the company to see the availability of stock of goods still using a manual system that requires a lot of time and accuracy. Therefore this inventory information system is expected to solve the problem. In this study produced an inventory information system design application that can produce an inventory report. It is expected that with this research, it will facilitate the process of monitoring the stock of goods entering and exiting goods. This research uses UML as a tool and PHP as a programming language in the design of a salon inventory system.Kata kunci: Design, System, Information, Inventory, UML